(untitled) (Archaeologia Adriatica, 2014)
C. Patsch found two votive monuments dedicated to the deity Armatus during the excavations in Karaula in Duvno in 1896. Most scholars accepted his opinion that Armatus was a local deity although Patsch did not mention function or character of the mentioned deity. In this work we will try to give more complete review of the mentioned deity, theses and arguments regarding his autochonous origin, and offer different opinions about his function and character.